Barron's essential words for the TOEIC - Lougheed, Lin, 1946-; Barron's Educational Series, Inc. (Hauppauge, N.Y. : Barrons Educational Series, Inc., 2017)
This test preparation book focuses on 600 words commonly used on the TOEIC. Words are taught in 50 vocabulary-building lessons that focus on American English as it is used in today's business, industry, communications, and cultural activities. All activities are formatted like the actual questions on the TOEIC exam and help students develop test-taking skills. Examples of practical English usage touch on such subjects as contracts, marketing, banking, and personnel, among many other activities. Additional exercises focused to help TOEIC test-takers expand their English vocabulary in areas related to cultural activities, such as movies, music, and art. Each lesson presents 12 target words with definitions, and then uses them in several different contexts. Practice exercises follow every lesson, and a quiz follows every five lessons to test students' expanding skills in English word usage. Recommendations for web-based study activities will further help the students increase their vocabulary. New in this edition is a practice TOEIC test based on the actual exam. The enclosed MP3 CD provides essential help in pronunciation and listening comprehension and comprises audio prompts for all of the listening comprehension exercises and conversations and talks featuring North American, British, and Australian accents.-- Publisher's description.
What the Book Is About -- How to Use This Book -- Strategies to Improve Your Vocabulary -- Study Contract -- Strategies to Practice Your Vocabulary -- LESSONS 1-5 GENERAL BUSINESS -- 1. Contracts -- 2. Marketing -- 3. Warranties -- 4. Business Planning -- 5. Conferences -- Word Review #1 -- LESSONS 6-10 OFFICE ISSUES -- 6. Computers and the Internet -- 7. Office Technology -- 8. Office Procedures -- 9. Electronics -- 10. Correspondence -- Word Review #2 -- LESSONS 11-15 PERSONNEL -- 11. Job Advertising and Recruiting -- 12. Applying and Interviewing -- 13. Hiring and Training -- 14. Salaries and Benefits -- 15. Promotions, Pensions, and Awards -- Word Review #3 -- LESSONS 16-20 PURCHASING -- 16. Shopping -- 17. Ordering Supplies -- 18. Shipping -- 19. Invoices -- 20. Inventory -- Word Review #4 -- LESSONS 21-25 FINANCING AND BUDGETING -- 21. Banking -- 22. Accounting -- 23. Investments -- 24. Taxes -- 25. Financial Statements -- Word Review #5 -- LESSONS 26-30 MANAGEMENT ISSUES -- 26. Property and Departments -- 27. Board Meetings and Committees -- 28. Quality Control -- 29. Product Development -- 30. Renting and Leasing -- Word Review #6 -- LESSONS 31-35 RESTAURANTS AND EVENTS -- 31. Selecting a Restaurant -- 32. Eating Out -- 33. Ordering Lunch -- 34. Cooking as a Career -- 35. Events -- Word Review #7 -- LESSONS 36-40 TRAVEL -- 36. General Travel -- 37. Airlines -- 38. Trains -- 39. Hotels -- 40. Car Rentals -- Word Review #8 -- LESSONS 41-45 ENTERTAINMENT -- 41. Movies -- 42. Theater -- 43. Music -- 44. Museums -- 45. Media -- Word Review #9 -- LESSONS 46 -- 50 HEALTH -- 46. Doctor's Office -- 47. Dentist's Office -- 48. Health Insurance -- 49. Hospitals -- 50. Pharmacy -- Word Review #10 -- TOEIC Model Test -- Answer Key for TOEIC Model Test.
With 1 computer optical disc. Kept in the special collection.
Accompanying MP3 CD comprises audio prompts for all of the listening comprehension exercises and conversations and talks featuring North American, British, and Australian accents.
Includes index.
Keywords: Test of English for International Communication -- Study guides; English language -- Textbooks for foreign speakers; English language -- Examinations -- Study guides; Vocabulary -- Examinations -- Study guides; English language -- Sound recordings for foreign speakers